Two-step purification strategy for enhanced recovery of recombinant hepatitis B surface antigen from Pichia pastoris - Tam, Yew Joon; Allaudin, Zeenathul Nazariah; Rezaei, Morvarid Akhavan; Mohd Lila, Mohd Azmi; Bahaman, Abdul Rani; Lo, Sewn Cen; Tan, Joo Shun; Hani, Homayoun (Taylor & Francis, 2016)
Univariate screening on factors affecting the purification performance of recombinant hepatitis B surface antigen (HBsAg) on ion exchange chromatography (IEC) and size exclusion chromatography (SEC) and the establishment of a two-step purification strategy were performed. Amongst four IEC adsorbents examined, the use of Q Sepharose XL IEC adsorbent under optimized conditions together with optimized SEC purification was able to efficiently purify HBsAg. An established purification strategy comprising the two techniques further demonstrated adaptability for scale-up operations with a final total purification factor (PF) of 94.82 ± 16.20, HBsAg purity of 95.48% and recovery yield of 78.07%.